The Impact of Real Exchange Rate and Gross Domestic Product on Trade Balance of Lao-Thailand - CHANTHAMATH, Phetsamone; CHANTHAVONE, Thongphanh; HER, Pheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The objectives of this study are to analyze the effect of the real exchange rate of kip to baht and gross domestic product on the trade balance between Lao-Thai in both short-run and long-run effects. The time series data from 1990-2021 was usedand implied with the ARDL model. The stationary of each variable was tested by Augmented Dickey Fuller (ADF) method. The empirical analysis by the ARDL model show that there is a long-run relationship. In the long run, the real exchange rate and the gross domestic product of Thailand have a negative relationship with the trade balance at a statistical significance level of 0.01. Meanwhile, the gross domestic product of the Lao PDR has a positive relationship. In the short term, only the gross domestic product of Lao PDR has a negative relationship with the trade balance at a significance level of 0.05. The gross domestic product of Thailand has the most effect on the trade balance, followed by the gross domestic product of the Lao PDR and the real exchange rate of kip per baht has the least effect. The coefficient of speed in adjusting to the equilibrium point is equal to -0.784, which means that after shock, it will be able to adjust to the long run equilibrium by 78.4%.